The knowledge of health tourism among Malaysian - Ismail Zuriadah, Mahjom Nurhanie, Roshidi Ahmad Mohamad Ali, (Universiti Pendidikan Sultan Idris, 2009)
The knowledge of health tourism among Malaysian by Ismail Zuriadah, Mahjom Nurhanie, Roshidi Ahmad Mohamad Ali,